Comparison between lupus nephritis in HIV positive patients and HIV associated immune complex glomerulonephritis with “lupus–like” features: a clinicopathologic study - Mathaba, Margaret Masala (My University, 2024)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease seen commonly in black females of childbearing age. More than half of the patients present with renal disease or lupus nephritis complications. Coinfection with HIV in patients with lupus nephritis is rare. Despite Africa having the highest rate of HIV infection in the world, and there is no available data on the coexistence of HIV and Lupus nephritis. HIV is associated with a wide spectrum of renal diseases, including “lupus-like” HIV-Associated Immune Complex Kidney Disease (HIVICK). The most prevalent renal lesions in “lupus-like” HIVICK is diffuse proliferative lupus nephritis Objectives: This study aimed to compare and correlate the demographics, epidemiology, pathological and clinical findings of HIV positive patients with lupus nephritis and those with “lupus-like” HIVICK. Methods: This retrospective chart review study was conducted at the Charlotte Maxeke Johannesburg Academic Hospital in 5 years (2014-2018). We reviewed case reports that met our criteria for cases with lupus nephritis and cases with “lupus-like” HIVICK and allocated a lupus class according to the report findings. Results: Out of 2174 renal reports, 25(1.14%) patients were diagnosed with lupus nephritis and nine (0.41%) with “lupus-like” HIVICK. There were significant differences in age, serology (urea and creatinine), clinical presentation and lupus class. Conclusion: The occurrence of both HIV associated lupus nephritis and ‘lupus like’ HIVICK is rare. In our setting, the former is more common than the latter. We observed clinical and pathological differences which may be used to diagnose these disease entities.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) to the Faculty of Health Sciences, University of the Witwatersrand, School of Pathology, Johannesburg, 2023
Keywords: Lupus nephritis; Systemic lupus erythematosus; South Africa; HIV; SDG-3: Good health and well-being